Translational Regulation of Utrophin by miRNAs - Basu, Utpal (Public Library of Science, 2011)
BACKGROUND: Utrophin is the autosomal homolog of dystrophin, the product of the Duchenne Muscular Dystrophy (DMD) locus. Its regulation is of therapeutic interest as its overexpression can compensate for dystrophin's absence in animal models of DMD. The tissue distribution and transcriptional regulation of utrophin have been characterized extensively, and more recently translational control mechanisms that may underlie its complex expression patterns have begun to be identified. METHODOLOGY/PRINCIPAL FINDINGS: Using a variety of bioinformatic, molecular and cell biology techniques, we show that the muscle isoform utrophin-A is predominantly suppressed at the translational level in C2C12 myoblasts. The extent of translational inhibition is estimated to be ∼99% in C2C12 cells and is mediated by both the 5′- and 3′-UTRs of the utrophin-A mRNA. In this study we identify five miRNAs (let-7c, miR-150, miR-196b, miR-296-5p, miR-133b) that mediate the repression, and confirm repression by the previously identified miR-206. We demonstrate that this translational repression can be overcome by blocking the actions of miRNAs, resulting in an increased level of utrophin protein in C2C12 cells. CONCLUSIONS/SIGNIFICANCE: The present study has identified key inhibitory mechanisms featuring miRNAs that regulate utrophin expression, and demonstrated that these mechanisms can be targeted to increase endogenous utrophin expression in cultured muscle cells. We suggest that miRNA-mediated inhibitory mechanisms could be targeted by methods similar to those described here as a novel strategy to increase utrophin expression as a therapy for DMD.